Development Of Optimized Chalcone-Based Small Molecules As JAK Inhibitors For Rheumatoid Arthritis Treatment - Devesh Sharma; Raj K. Prasad, Shweta Srivastava; Harsh Vardhan Singh; Abhay Pandey (Revista Electronica de Veterinaria, 2024)
Rheumatoid arthritis (RA) is a persistent autoimmune disorder that affects around 0.5-1% of the global population. The design and optimization of small molecule chalcone derivatives as JAK inhibitors encompass a series of essential stages. The design of chalcone derivatives was facilitated using the Chemdraw and ADMET Lab 3.0 studies conducted by Swiss ADME. Molecular docking, acute prediction, and derivatives analysis were conducted on several compounds related to chalcone derivatives using the Schrodinger Glide 30.8 software with proteins ligands JAK 3 Kinase (PDB-6NY4).Quantification of docking score, ADMET analysis, prediction of acute toxicity, and determination of structural position of ligands in the active JAKs site enzymes. The C compounds have a binding affinity (Docking score: -9.158), VAL901, LEU822, PHE817, ILE816, LEU822, VAL889, & TYR891 showed hydrophobic interaction with protein, charge (positive) ARG899, ARG820 & ARG887, charge (negative) GLU818, GLU819, polar nature is the HIS821, SER890 & THR815, and water GLY892, GLY888 bind to each other and show of protein affinity and the M compounds has a binding affinity (Docking score: -9.084), LEU875, ILE872, TYR886, VAL889, PHE817, MET902, VAL901, LEU900, and LEU898.